Small area variation in crime effects of COVID-19 policies in England and Wales. (July 2021) - Langton, Samuel; Dixon, Anthony; Farrell, Graham
Abstract: Purpose: The aim of this study is to examine small area variation in crime trajectories during the COVID-19 pandemic in England and Wales. While we know how police-recorded crime responded to lockdown policies at the 'macro' level, less is known about the extent to which these trends were experienced uniformly at localized spatial scales. Methods: Longitudinal k-means clustering is used to unpick local area variation in police notifiable offences across England and Wales. We describe the clusters identified in terms of their spatial patterning, opportunity structures and crime type profile. Results: We find that in most small areas, crime remained fairly stable throughout the pandemic. Instead, a small number of meso-level areas contributed a disproportionately large amount to the macro-level trend. These were typically city centers with plentiful pre-pandemic crime opportunities, dominated by theft and shoplifting offences. Conclusion: Findings offer support for opportunity theories of crime and for a mobility theory of crime during the pandemic. We explore potential implications for policy, theory and further research. Highlights: Studies showing macro-level crime declines during the coronavirus pandemic have not tended to examine how this occurred at the local area level. We find that crime in most small areas remained fairly stable but a small number of meso-level areas contributed disproportionately to the macro-level trend. The small areas that changed most were city centers dominated by theft and shoplifting offences. The findings support crime opportunity theories and the mobility theory of crime change during the pandemic.